Determination of the Electron Temperature of the Plasma - Mikhailov, V (Current Research Progress in Physical Science Vol. 4, 2024)
The aim of the work was to obtain analytical dependences of the electron temperature of the plasma surrounding the spacecraft on the descent trajectory. The radiometric diagnostic method was used. As a result, the desired dependencies were obtained, as well as expressions characterizing diagnostic errors. The results of calculating the errors in determining the electronic plasma temperature depending on the type of radiometer and matching the antenna of the onboard radiometer are presented. The analysis of the obtained results is given.